2017
DOI: 10.1016/j.rse.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Modeling gross primary production of paddy rice cropland through analyses of data from CO2 eddy flux tower sites and MODIS images

Abstract: Accurate information on the gross primary production (GPP) of paddy rice cropland is critical for assessing and monitoring rice growing conditions. The eddy co-variance technique was used to measure net ecosystem exchange (NEE) of CO 2 between paddy rice croplands and the atmosphere, and the resultant NEE data then partitioned into GPP (GPP EC ) and ecosystem respiration. In this study, we first used the GPP EC data from four paddy rice flux tower sites in South Korea, Japan and the USA to evaluate the biophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 119 publications
(138 reference statements)
6
24
0
Order By: Relevance
“…Enhanced vegetation index (EVI) is related to vegetation canopy 32 ( Supplementary Fig. 13), and has been used to estimate gross primary production of paddy rice 33 . We used MODISbased EVI as a proxy for rice plant growth to quantify the seasonal relationship between the paddy rice growth and atmospheric CH 4 concentration in a year.…”
Section: (Supplementarymentioning
confidence: 99%
“…Enhanced vegetation index (EVI) is related to vegetation canopy 32 ( Supplementary Fig. 13), and has been used to estimate gross primary production of paddy rice 33 . We used MODISbased EVI as a proxy for rice plant growth to quantify the seasonal relationship between the paddy rice growth and atmospheric CH 4 concentration in a year.…”
Section: (Supplementarymentioning
confidence: 99%
“…where T min , T max , and T opt are minimum, maximum, and optimal temperature for photosynthesis, respectively. As wetland plants can photosynthesize across a broad range, T min and T max were set to 0 °C and 50 °C (Larcher, 2003), and we used a value of 22 °C for T opt based on the relationship between GPP and air temperature (Xin et al, 2016). For Landsat-retrieved VIs only, W scalar was calculated using a simple approach utilizing a water-sensitive vegetation index (Oikawa et al, 2017;Xiao et al, 2004) (8) where LSWI max is the maximum land surface water index (LSWI; Table 1) within the growing season, and was estimated separately for each year (Kang et al, 2014).…”
Section: Light Use Efficiency Modelsmentioning
confidence: 99%
“…Running et al, 2004;Running et al, 2000). While the MODIS GPP algorithm provides reasonable spatio-temporal patterns and variability across a diverse range of biomes and climate types (Heinsch et al, 2006), it has been shown to underestimate GPP in natural wetlands (Kang et al, 2014) and flooded rice agriculture (Xin et al, 2017), which has been attributed to the climate data, pixel heterogeneity, and the light use efficiency parameter used in the MODIS GPP model. The coarse spatial resolution (1 km) of MODIS can also be problematic for estimating wetland GPP as these ecosystems can be small in size, and highly distributed, fragmented or disconnected from other habitat types (Byrd et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of VPM model is driven by time series images from the by MODIS and climate data (photosynthetically active radiation (PAR); air temperature). GPP data have been evaluated at many CO 2 eddy flux tower sites [24][25][26][27][28] and the results show that the VPM produces very good consistency with tower-derived GPP. The time series GPP data were acquired from at the University of Oklahoma's Earth Observation and Modeling Facility (http://www.eomf.ou.edu/ accessed on 13 December 2019).…”
Section: Gross Primary Production (Gpp) Data From the Data-driven Vegmentioning
confidence: 99%